Integration Of Ethical Values In Sports Learning In Schools - Abidin, Zaenal; Ahmad, Masduki; Suryadi, Suryadi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to analyze the integration of ethical values ​​in sports learning in schools through a literature review approach. Ethical values, such as sportsmanship, fairness, responsibility, and cooperation, are important components in sports learning that can shape students' characters. However, the implementation of these values ​​in learning practices often faces various challenges, such as pressure on competitive results, limited teacher training, and minimal curriculum support. This review explores the concept, model, and strategy of integrating ethical values ​​in sports learning based on relevant literature. The results of the analysis show that value-based learning models, such as Teaching Personal and Social Responsibility (TPSR), have succeeded in increasing ethical awareness and positive behavior of students in various contexts. In addition, this study highlights the importance of the role of teachers as value facilitators, as well as the need for institutional support to systematically integrate ethical values ​​into the sports education curriculum. This review also identifies gaps in research related to the implementation of ethical values ​​in developing countries, including Indonesia, which has unique cultural characteristics and education systems. This study recommends the development of educational policies that focus on strengthening ethical values ​​in sport, intensive training for teachers, and further studies that measure the impact of ethical values ​​integration on students' character development